Zumba Exercise Training to Train Motor Movement & VO2 Max - Andi Nurcahyo; Faisal Yusuf; Diah Aryati Puji Lestari; Prima Januar Sastrawirya (Faculty of Engineering, Universitas Semarang, 2025)
This training aims to improve motoric movements and exercise, especially Zumba exercises, for health and to increase people's interest because Zumba exercise can improve motor skills. It is hoped that this training will increase public knowledge about the importance of physical fitness and exercise in increasing VO2 Max. The training carried out is face-to-face training with a descriptive approach. To achieve motor movement, VO2 Max, this training uses quantitative descriptive research methods where researchers are directly involved in actively meeting, observing, and analyzing participant data regarding the value of Zumba exercise and motor movement before doing Zumba exercise and after doing Zumba exercise. The results of this activity showed an increase of 54.29% based on the pre-test and post-test. Components that influence this increase include the benefits of motoric movements, heart rate, calories burned, VO2 Max value, and its benefits for the body. Through energetic Zumba gymnastics, it can encourage motoric movements which can then increase the VO2 Max value. The VO2 Max value is one of the indicators of physical fitness and the effectiveness of the exercise performed.